Intervenciones de enfermería en la prevención de infecciones de heridas quirúrgicas por cesárea en el área de maternidad del Hospital Provincial Martin Icaza de la provincia los Ríos ciudad de Babahoyo durante el periodo de mayo a septiembre 2019. - Neira García, Maryury Melina (2019)
INTRODUCTION: Caesarean section is currently considered a public health problem because this procedure is being used in a greater percentage than required. Caesarean section surgical wound infections are one of the causes of maternal morbidity and tend to occur mostly because adequate post-surgical interventions are not used. OBJECTIVE: Analyze nursing interventions for the prevention of infections in surgical wounds by caesarean section. METHODOLOGY: The process of this research is based on a deductive, descriptive, analytical, observational study by applying surveys to 70 post-cesarean postpartum to identify the various nursing interventions applied for the prevention of infections in the surgical site and thus determine the possible causes that could cause the appearance of these infections. RESULTS: Once the results are analyzed, a discussion of them is presented, which is based on the assumptions raised as hypotheses, we can mainly know that the risk factors for the occurrence of HQ infections more frequently in the Martín Icaza hospital in the city of Babahoyo are those mothers who are overweight and gestational diabetes. CONCLUSIONS: Through the investigation carried out, we were allowed to take 70 hospitalized mothers as a sample, to carry out the data collection, it was done through surveys that went directly to the mothers, which allowed us to obtain detailed statistical data below.